2014
DOI: 10.1128/aac.02048-13
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Multiresistant Gram-Negative Bacteria to Fosfomycin and Performance of Different Susceptibility Testing Methods

Abstract: Fosfomycin may be a treatment option for multiresistant Gram-negative bacteria. This study compared susceptibility methods using 94 multiresistant clinical isolates. With agar dilution (AD), susceptibilities were 81%, 7%, 96%, and 100% (CLSI) and 0%, 0%, 96%, and 30% (EUCAST), respectively, for Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Enterobacter spp. Categorical agreement between Etest and AD for Enterobacteriaceae and A. baumannii was >80%. Disk diffusion was adequate only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 22 publications
4
28
2
1
Order By: Relevance
“…On the other hand, particularly for P. aeruginosa, a recent study suggested that broth microdilution is a reliable method, whereas no concordance was observed between agar dilution and disk diffusion/Etest (61). Finally, a recent study evaluating agar dilution, disk diffusion, and Etest for contemporary multidrug-resistant (MDR) Gram-negative pathogens suggested that disk diffusion had poor performance for Acinetobacter baumannii and Enterobacteriaceae and that Etest performed poorly for all tested pathogens (64). The available MICs and zone diameter breakpoints suggested by CLSI and EUCAST for specific bacteria are presented in Table 1.…”
Section: Susceptibility Testing Methodologymentioning
confidence: 99%
“…On the other hand, particularly for P. aeruginosa, a recent study suggested that broth microdilution is a reliable method, whereas no concordance was observed between agar dilution and disk diffusion/Etest (61). Finally, a recent study evaluating agar dilution, disk diffusion, and Etest for contemporary multidrug-resistant (MDR) Gram-negative pathogens suggested that disk diffusion had poor performance for Acinetobacter baumannii and Enterobacteriaceae and that Etest performed poorly for all tested pathogens (64). The available MICs and zone diameter breakpoints suggested by CLSI and EUCAST for specific bacteria are presented in Table 1.…”
Section: Susceptibility Testing Methodologymentioning
confidence: 99%
“…Currently data on fosfomycin PK in critically ill patients are scarce; therefore, no accurate dose recommendation can be made [60]. The recent renewed interest on fosfomycin is related to its in vitro activity against XDR and PDR K. pneumonia; its activity against P. aeruginosa is moderate and is absent against A. baumannii [61,62]. Early data have raised concerns about rapid development of resistance to fosfomycin when used as a monotherapy for systemic infections.…”
Section: • Fosfomycinmentioning
confidence: 99%
“…Recent studies have shown a synergy of fosfomycin with carbapenems (the combination prevents the emergence of resistance), aminoglycosides, quinolones and variably with β-lactams [63,64]. Furthermore, complicating its use in daily clinical practice, susceptibility testing is not yet reliably supported by routine methods; an Epsilometer-test (E-test) has been recently developed with acceptable concordance with the agar dilution method; however, this still requires extra laboratory time [61]. The in vivo effectiveness of fosfomycin against MDR pathogens is largely unknown.…”
Section: • Fosfomycinmentioning
confidence: 99%
“…Addition of glucose-6-phosphate is required under the EUCAST guidelines as well. The testing methods (agar dilution, disk diffusion and Etest) appear to correlate well among contemporary gram-negative clinical isolates, with some Etest and agar dilution results not in essential agreement but not resulting in significant major or very major error rates [36], while some data suggest that disk diffusion testing and Etest may undercall resistance for carbapenem-resistant P. aeruginosa [37] and Enterobacteriaceae [38]. …”
Section: Susceptibility Testingmentioning
confidence: 99%
“…For Pseudomonas aeruginosa and Stenotrophomonas maltophilia , the MICs cluster around 64 µg/ml, thus the interpretation will depend on the susceptibility breakpoint applied [36, 37, 40]. Acinetobacter baumannii and Morganella morganii are mostly resistant to fosfomycin [36, 40, 44], thus its use would only be considered in the context of combination therapy, especially for A. baumannii .…”
Section: Spectrum Of Activitymentioning
confidence: 99%